THE IMPORTANCE OF SPEAKING RUSSIAN LANGUAGE AROUND THE WORLD (Journal of Science-Innovative Research in Uzbekistan, 2024)
In this article, I will talk about how many people speak Russian in the world and the potential of teaching Russian in schools. I have given examples of the widespread promotion of the Russian language as a subject in kindergartens, schools, colleges and even higher education institutions.